Police shooting mortality: Investigating individual, incident, and contextual factors differentiating fatal and non-fatal police shootings - Sheppard, Keller (Journal of ethnicity in criminal justice, 2022)
Research on relevance of race and community context for police shooting mortality is underdeveloped. We collected data on 623 police-involved shootings in the state of Texas to examine which incident- and county-level factors are associated with shooting outcomes. In doing so, we incorporate a novel incident-level variable: distance from incident to trauma hospitals. Results from hierarchical linear models suggest that the lethality of police-involved shootings is positively correlated with the number of officers and citizen possession a deadly weapon. Additional models indicate that community violent crime rates are the only contextual factor associated with both fatal and non-fatal shootings.